Potential of Rice Husk Brackets as A New Alternative Sea Water Distillation into Clean Water - Syarif, Humayatul Ummah; Ali, Muhammad yusuf; Thamrin, Ahmad (Yayasan Banu Haji Samsudin, 2024)
The need for clean water for people in Indonesia is increasing, especially in coastal areas, while the availability of clean water is very limited. One of the efforts made to anticipate is by utilizing sea water with a solar distillation system. In this study, the absorber used was rice husk briquettes. Various distillation technologies have been developed, but distillation technology with solar energy sources is still experiencing various obstacles so further technology and research are needed. To develop this technology, research was conducted with the aim of (1) producing a design of the thickness and density of rice husk briquettes in a seawater distillation system. (2) to produce clean water for each pair of thickness and density of rice husk briquettes through a seawater distillation system. (3) Knowing how much heat absorption efficiency is by using a rice husk briquette absorber. The research method used is a comparative method, which is a comparative study, where in this study the thickness and density of rice husk briquettes are compared. The data analysis method used the descriptive method. The parameters to be analyzed are plate temperature (Tp), glass temperature (Tg), water temperature (tw), basin room temperature (Tsv), ambient temperature (Ta) and distilled water (AT), area of absorbent plate (Ac), Collector and distillation efficiency. This research resulted in a design for the distillation of seawater into clean water using an absorber plate (absorber) of rice husk briquettes which can increase the production of clean water.